Copy number and transcriptome alterations associated with metastatic lesion response to treatment in colorectal cancer. Issue 4 (1st May 2021) - Gambaro, Karen; Marques, Maud; McNamara, Suzan; Couetoux du Tertre, Mathilde; Diaz, Zuanel; Hoffert, Cyrla; Srivastava, Archana; Hébert, Steven; Samson, Benoit; Lespérance, Bernard; Ko, Yoo‐Joung; Dalfen, Richard; et al.
Abstract: Background: Therapeutic resistance is the main cause of death in metastatic colorectal cancer. To investigate genomic plasticity, most specifically of metastatic lesions, associated with response to first‐line systemic therapy, we collected longitudinal liver metastatic samples and characterized the copy number aberration (CNA) landscape and its effect on the transcriptome. Methods: Liver metastatic biopsies were collected prior to treatment (pre, n = 97) and when clinical imaging demonstrated therapeutic resistance (post, n = 43). CNAs were inferred from whole exome sequencing and were correlated with both the status of the lesion and overall patient progression‐free survival (PFS). We used RNA sequencing data from the same sample set to validate aberrations as well as independent datasets to prioritize candidate genes. Results: We identified a significantly increased frequency gain of a unique CN, in liver metastatic lesions after first‐line treatment, on chr18p11.32 harboring 10 genes, including TYMS, which has not been reported in primary tumors (GISTIC method and test of equal proportions, FDR‐adjusted p = 0.0023). CNA lesion profiles exhibiting different treatment responses were compared and we detected focal genomic divergences in post‐treatment resistant lesions but not in responder lesions (two‐tailed Fisher's Exact test, unadjusted p ≤ 0.005). The importance of examining metastatic lesions is highlighted by the fact that 15 out of 18 independently validated CNA regions found to be associated with PFS in this study were only identified in the metastatic lesions and not in the primary tumors. Conclusion: This investigation of genomic‐phenotype associations in a large colorectal cancer liver metastases cohort identified novel molecular features associated with treatment response, supporting the clinical importance of collecting metastatic samples in a defined clinical setting. Abstract : Graphical Abstract and Graphical Headlights Liver metastatic lesions from colorectal cancer patients were collected before and after first‐line standard chemotherapy and comprehensively profiled with the objective to assess the genomic impact of systemic therapy and investigate association with response and survival. This study allowed identification of novel CNAs having an impact on the transcriptome with a potential prognostic value in patients with colorectal cancer.